Sociodemographic and health factors associated with chronic pain in institutionalized elderly - Maria Helena Barbosa; Alison Fernandes Bolina; Jordânia Lumênia Tavares; Aldenora Laísa Paiva de Carvalho Cordeiro; Raíssa Bianca Luiz; Karoline Faria de Oliveira (Universidade de São Paulo, 2014)
OBJECTIVES: to characterize chronic pain in institutionalized elderly and verify the associated factors.METHOD: observational, cross-sectional and non-experimental study with a quantitative approach. The study participants were 124 elderly living in Long-Term Care Institutions for the Elderly (LTCIs) in a city in Minas Gerais (Brazil). Approval for the project was obtained from the Research Ethics Committee. The elderly's clinical and sociodemographic variables and pain-related aspects were assessed. The data were analyzed through descriptive statistics and bivariate analysis (chi-squared).RESULTS: the prevalence of chronic pain corresponded to 58.1%; for more than 10 years (26.4%); in lower limbs (31.9%); characterized as "twinges" (33.3%); 33.3% adopted medication treatment; the pain did not improve (41.7 %); or worsen (34.7 %). It was evidenced that elderly aged 60├ 70 old had 70% less chances of chronic pain than those aged 80 years and older (p=0.018).CONCLUSION: institutionalized elderly have a high prevalence of chronic pain, mainly in the lower limbs. No factors of pain improvement or worsening were identified and medication was evidenced as the preferred treatment. Age showed to be associated with the presence of pain. It is considered important to accomplish multiprofessional actions at the LTCIs to guide prevention and rehabilitation actions of the pain episodes in these elderly.